Ozonated Aloe vera Oil Effective Increased the Number of Fibroblasts and Collagen Thickening in the Healing Response of Full-Thickness Skin Defects - Ahsanu Taqwim Hidayat; Muhamad Thohar Arifin; Muhammad Nur; Muflihatul Muniroh; Neni Susilaningsih (Hindawi Limited, 2021)
Objective. This study aimed to examine the effectiveness of ozonated Aloe vera oil on the wound healing response of full-thickness defect tissue in Sprague-Dawley rats, assessed by collagen thickness and the number of fibroblasts. Methods. This was an experimental research method using control groups and treatment groups with a posttest only control group design. The results showed that collagen thickness in wounds tended to increase, assessed on day 3 and day 7 using Masson's trichrome staining and microscopic evaluation. Results. There was a significant difference in the number of fibroblasts between the two control and treatment groups on days 3 and 7 tested using one-way Kruskal-Wallis test, with a value of p=0.001p<0.05, resulting in a significant difference in wound size reduction between the groups. Further post hoc analysis using the Mann-Whitney test indicated a significant difference between the control groups and the treatment groups (P0, P1 versus P3, P4, P5, P8, P9, and P10) with a value of p=0.009p<0.05. Conclusions. Ozonated Aloe vera oil is effective in increasing the healing response of full-thickness defects, leading to the increase in the number of fibroblasts and collagen thickening that in turn accelerates wound healing in Sprague-Dawley rats.